Nodules and leguminous crops - Ingman, C.B. (My University, 1897)
Introduction: There are many reasons ascribed for the lack of progress in agriculture. Not the least of these is ignorance of the chemistry of the soil and the conditions of plant growth. Farmers are beginning to understand that no soil, however rich, can produce crops year after year without loss of fertility, unless something be returned to replace the elements taken away by the crops. Chemists have found that there are about eleven elements necessary to plant growth and that all normal soils there is found a sufficient of all these except three. The three elements usually occurring in insufficient quantities are potassium, phosphorus, and nitrogen. Of the first two, potassium and phosphorus, it may be said, that when they become deficient, the only to return them to the soil is in the form of a fertilizer. But nitrogen may be returned in a much easier and more economical manner as we shall presently describe.
Citation: Ingman, C.B. Nodules and leguminous crops. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Agriculture; Legumes; Nitrogen; Theses; Manuscripts (documents)